Applying Marketing Strategic Planning Tools to Evaluate the Growth Potential of Ukraine’s Dairy Industry - Senyshyn, Oksana; Kundytskyj, Oleksandr; Khich, Roman; Goryn, Marta; Chopko, Natalia; Zamroz, Marianna (Research on World Agricultural Economy, 2025)
This study aims to examine the use of marketing tools for strategic planning to assess the development prospects of Ukraine’s dairy industry, utilizing SWOT analysis, taxonomic analysis and scenario modelling methodologies. On the one hand, the author has chosen the SWOT-analysis method, the main goal of which is to determine the positioning of the dairy industry by evaluating its strengths and weaknesses, opportunities, and threats to select and identify the best strategies for its development. On the other hand, a comprehensive methodology for evaluating the dairy industry in Ukraine was used, specifically the taxonomic analysis and scenario modelling methods, which allowed the author to calculate the efficiency coefficient. As a result of applying strategic planning methodologies, the instability of the taxonomic indicator during 2003–2022 was demonstrated, which is caused by the following main reasons: military actions in Ukraine by the Russian aggressor, the noncompliance of certain types of dairy products with EU technical standards, among others. The practical value of scientific research is that it proposes the utilization of marketing strategies to assess the potential for development of the Ukrainian dairy industry, the combination of the SWOT method and taxonomy is particularly significant. Based on the SWOT analysis, a marketing strategy was proposed that specifically involved: a marketing innovation strategy, which would allow for the future enhancement of both design and packaging, as well as the reduction of the cost of dairy products.